2013
DOI: 10.1149/04701.0157ecst
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Pre-Treatment On Electrochemical Properties of CeO2 thin Films Deposited by R.F. Sputtering On AA7075 Aluminum Alloy

Abstract: Nanocrystalline CeO2 coatings were grown on AA7075 aluminum alloy substrates using RF magnetron sputtering and analyzed as protective barriers inhibiting the pitting corrosion reactions in chloride medium. Special attention was placed in the effect of alkaline and acid pretreatments on structural, morphological and electrochemical properties of CeO2 coatings. For this purpose, a CeO2 target under Ar atmosphere was used at room temperature employing different powers. The as-prepared films were characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…The impact of such factors on the corrosion performance of CeOCs deposited by chemical methods has been reported in the literature [3,14,23,24]. However, few studies have focused on the corrosion performance of CeOCs deposited by magnetron sputtering [5,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of such factors on the corrosion performance of CeOCs deposited by chemical methods has been reported in the literature [3,14,23,24]. However, few studies have focused on the corrosion performance of CeOCs deposited by magnetron sputtering [5,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Brachetti-Sibaja et al [25,26] investigated deposition parameters including target power, substrate temperature and the surface pretreatments for CeOCs with thicknesses in the range of 20 nm to 350 nm. A systematic study of the effects of coating thickness between 100 nm to over 1000 nm on the morphology, structure, mechanical property and corrosion performance of sputter deposited CeOCs has not been published.…”
Section: Introductionmentioning
confidence: 99%
“…5,[17][18][19][20][21] Fewer studies have been reported using physical vapor deposition (PVD) techniques to deposit CeOCs on Al alloy substrates. [22][23][24][25] Previous studies showed that magnetron sputtering deposited CeO 2 coatings could provide cathodic inhibition for Al alloys in saline solution by acting as a barrier between Al alloy substrates and corrosion media. Pitting corrosion occurred at the electrochemical potential for both CeO 2 coated and uncoated Al 2024-T3 alloy samples, suggesting active anodic pitting corrosion behavior.…”
mentioning
confidence: 99%
“…Pitting corrosion occurred at the electrochemical potential for both CeO 2 coated and uncoated Al 2024-T3 alloy samples, suggesting active anodic pitting corrosion behavior. [22][23][24][25] In addition, Al-Ce alloy coatings deposited by magnetron sputtering 26,27 and ionic liquid 13 methods have been shown to improve the corrosion performance of Al alloys. Attempts to incorporate Al atoms into sputter deposited CeO 2 oxide coating to modify coating structure and corrosion performance have not been reported.…”
mentioning
confidence: 99%
“…Commercial PU is commonly used for wood and metal finishing applications, giving brightness, toughness and wear resistance to materials. It is important to remark that CeO 2 used as a coating or chemical conversion treatment has been frequently reported by different researchers using conventional techniques such as dip-coating, sol-gel, and more recently sputtering [ 62 , 63 , 64 , 65 , 66 ]. However, this work proposes a novel synthesis of hybrid coatings with ceria through reinforcing crosslinks during the curing process of water-based polyurethane.…”
Section: Resultsmentioning
confidence: 99%